Development of buffalo meat patties incorporated with cauliflower stem powder: An approach towards quality and shelf life improvement - Haque, Abdul; Ahmad , Saghir (Journal of Postharvest Technology, 2022)
Since meat products taste great and have superior nutritious properties, their popularity has skyrocketed in recent years. In this investigation, cauliflower stem powder was added to buffalo meat patties to test its overall quality and sensory parameters. For this, cauliflower stem powder was added to patties in different proportions 2 %, 4 %, and 6 % by weight. The samples incorporated with cauliflower stem powder showed an improvement in water-holding capacity and cooking yield. The thickness of the patties increased while the diameter decreased with the incorporation of cauliflower stem powder. The moisture content, protein content, crude fiber, and ash content of patties increased while the pH and TBA number decreased. The lipid oxidation decreased in treated samples, as shown by the reduced TBA number compared to the control sample. The patties became redder and darker than the control patty, as measured by instrumental color evaluation. The sensory analysis results showed that 6% of cauliflower stem powder could be successfully incorporated into the patties without affecting their overall quality.